Anemia Management in Dialysis Dependent and Non-Dialysis Dependent Chronic Kidney Disease Patients – Prospective Observational Study in A Tertiary Care Hospital in South India - Baiju, Anulakshmi Perumthattuthara; Asan, Farisa Thottunkal; Fathima, Nourin; Benny, Rini Rose; Joseph, Siby; Upendran, Binu (Indian Journal of Pharmacy Practice)
Background: Anemia is a common and significant complication of Chronic Kidney Disease (CKD). This study focuses on the change in haemoglobin levels of CKD patients during treatment with Erythropoietin stimulating agent (ESA)/Hypoxia Inducible Factor-Prolyl Hydroxylase Inhibitors (HIF-PHI) with or without Haematinics. Hypertension is a common adverse effect of erythropoietin treatment. Materials and Methods: A prospective study was conducted in Nephrology department of a tertiary care teaching hospital for six months. Patients were recruited based on inclusion and exclusion criteria. Results: The total sample in our study was 117, which is characterized by a male preponderance with 72 (61.5%). Among study population majority of patients 76 (65%) were undergoing Haemodialysis. Among four types of anaemia management drugs in non-dialysis patients a higher mean Hb change was noted in ESA+Hematinics in Hb range (9.1-10 g/dL), which is 1.4. Whereas in ESA alone, the higher Hb change in the range (9.1-10 g/dL), was 0.86. In case of dialysis, a higher mean Hb change was noted in ESA+Hematinics in the Hb range (7.1 – 8 g/dL), which is 1.43, Whereas in ESA alone, the Hb change in the baseline range (7.1 – 8 g/dL), was 0.8. In case of dialysis patients, a statistically significant elevation was observed between pre and post systolic/diastolic BP (p value 0.01). The twice weekly ESA therapy required more modification in antihypertensive therapy than once weekly ESA dosing. In dialysis patients, majority of patients were prescribed with ESA+Hematinics and in non-dialysis, a greater number of patients were prescribed with hematinics alone. Conclusion: Anemia management was found to be better if Erythropoietin is supplemented with haematinics both in dialysis dependent and non-dialysis dependent CKD patients. ESA treatment required increases in the doses/frequency/ and add-on therapy of antihypertensive agents.
Keywords: Chronic Kidney Disease; Anemia; Erythropoietin Stimulating Agents; Hematinics